Design and synthesis of ordered periodical mesoporous organosilicas for various applications - Guo, Junfei (2013)
Periodical Mesoporous Organosilicas (PMOs) is a new class of solid mesoporous materials that have various applications in many fields such as gas storage, catalysis and sequestration of pollutants etc. Design and synthesize new PMOs for different applications--gas storage and catalysis--are of great importance for both materials research and industry. A novel pyridine urea (PU) precursor ligand was designed, synthesized and successfully incorporated into PMOs. The PU precursor functionalized PMOs was an excellent solid support for catalytic active species like palladium. The PU-PMOs supported palladium catalyst shows outstanding catalytic activity for Suzuki and Sonogashira cross coupling reactions while the PMOs do not exhibit significant adsorption ability for carbon dioxide. Another nitrogen rich ligand (NTT), with many amine and triazole groups was designed and synthesized. This NTT ligand was designed to have rate acceleration ability for copper catalyzed alkyne –azide cycloaddition (CuAAC) reaction to be incorporated into PMOs for carbon dioxide adsorption.